A sodium ion battery precursor and positive electrode material and preparation method thereof
Through a two-stage co-precipitation process, in the synthesis of sodium ion battery positive electrode materials, the problem of irregular precipitation of copper elements is solved by using different pH values and mixed complexing agents of ammonia and oxalic acid, forming a high-quality core-shell structure precursor, and improving the electrochemical performance and stability of the material.
Patent Information
- Application Number
- CN202410395526.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-02
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-04-02
AI Technical Summary
During the synthesis process, existing sodium ion battery positive electrode materials are prone to precipitation of a large number of irregular crystal nuclei of copper elements, resulting in problems such as deviation from the stoichiometric ratio from the design, poor spherical shape, loose interface contact, and low tap density.
A two-stage co-precipitation process is adopted, and when precipitating the core and shell, a mixed complexing agent with different pH values and ammonia and oxalic acid is used to promote the close complexation rate of each ion, improve the output rate of copper and iron, and form a core-shell structure precursor with a high specific surface area and a close contact between the core and shell interface.
The high spherical shape, controllable morphology, high tap density, and high capacity, long cycle life and good air stability of the precursor are achieved.
Smart Images

Figure CN118289836B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion battery materials, and in particular relates to a sodium ion battery precursor and a positive electrode material and a preparation method thereof. Background Art
[0002] With the rapid development of the lithium-ion battery industry, the market demand for lithium resources has gradually increased. In recent years, the shortage of lithium resources and the sharp fluctuations in raw material prices have hindered the further application of lithium-ion batteries to a certain extent. Compared with lithium-ion batteries, sodium resources are abundant in reserves, evenly distributed, and have low raw material costs, and have broad application prospects. Sodium-ion battery positive electrode materials include Prussian blue, polyanions, layered oxides and other types. Among them, layered oxide sodium-ion battery positive electrode materials have attracted much attention due to their high energy density and good cycle performance. Nickel-iron-manganese-based and copper-iron-manganese-based layered positive electrode materials have become research hotspots due to their low raw material prices and excellent performance. Nickel-iron-manganese-based layered positive electrode materials have high capacity, and copper-iron-manganese-based layered positive electrode materials have good air stability and cycle performance. The design and preparation of core-shell structured positive electrode materials with a nickel-iron-manganese-based core and a copper-iron-manganese-based shell can combine the advantages of both materials.
[0003] CN116111083A discloses a sodium ion positive electrode material with a core of sodium nickel iron manganese oxide and a shell of sodium copper iron manganese oxide. The patent uses ammonia water as a single complexing agent, and the same pH value is used in the preparation process of the core and the shell. 2 K sp The value is 2.2 x 10 -20 With Fe(OH) 2 、Ni(OH) 2 、Mn(OH) 2 The differences are 4, 5 and 7 orders of magnitude respectively, and the initial precipitation pH value is about 4.2 - 6.7, which is 0.8 - 3 different from the initial precipitation pH value of other hydroxides. Therefore, when ammonia water is used alone as a complexing agent and the same pH value is maintained, the synthesis of precursors containing four elements of copper, nickel, iron and manganese is likely to cause a large number of irregular crystal nuclei of copper element to precipitate, and there are problems such as phase deviation between the stoichiometric ratio and the design, poor sphericity, loose interface contact, and low tap density.
[0004] In view of this, the present invention adopts different pH values and complexing agents in the precipitation kernel and shell by two-stage coprecipitation, and the finished product has better sphericity. The first mixed complexing agent based on oxalic acid was developed. The chelating reaction complexing ability of oxalic acid with copper and ferrous ions is stronger, the product is stable, and the use of ammonia water can promote the complexing rate of each ion to be close, while ensuring that each ion is fully complexed. The output rate of copper and iron elements is improved. Avoid using ammonia water alone to cause a large number of irregular crystal nuclei of copper elements to precipitate, and using oxalic acid alone to cause the precursor to have many short rod-shaped primary particles, loose morphology, poor sphericity and other problems. The core-shell structure precursor prepared by the present invention has the advantages of high specific surface area, close contact between the kernel and the shell interface, high tap density, controllable morphology, good sphericity and high output rate, and the positive electrode material prepared by the precursor has the advantages of high capacity, long cycle life and good air stability. Summary of the invention
[0005] The present invention provides a core-shell structure precursor and a preparation method thereof in view of the problems existing in the prior art. The core of the precursor is nickel-iron-manganese hydroxide and the shell is copper-iron-manganese hydroxide. The precursor prepared by the method has uniform primary particle size, good secondary particle sphericity, high tap density, and controllable spherical particle size.
[0006] The present invention also provides a sodium ion positive electrode material and a preparation method thereof. The positive electrode material prepared by the method has good air stability and excellent electrochemical performance.
[0007] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0008] A method for preparing a sodium ion battery positive electrode material precursor comprises the following steps:
[0009] (1) preparing a mixed salt solution A of nickel, ferrous iron and manganese, a mixed salt solution B of copper, ferrous iron and manganese, mixed complexing agent solutions C and D of ammonia water and oxalic acid, an alkali solution and a reaction kettle bottom liquid, wherein the molar weight of oxalic acid in the complexing agent solution C accounts for 5-10% and the molar weight of ammonia water accounts for 90-95%; and the molar weight of oxalic acid in the complexing agent solution D accounts for 10-30% and the molar weight of ammonia water accounts for 70-90%;
[0010] (2) A mixed salt solution A, an alkali solution and a complexing agent solution C are introduced into a reactor containing the reactor bottom liquid in parallel, and the pH value is controlled to be 9-11 to carry out the first stage of coprecipitation reaction; and the particle size of the prepared material is D 50 After reaching 8-10μm, mixed salt solution B, alkali solution and complexing agent solution D are introduced into the reactor in parallel, and the pH value is controlled at 8.5-10.5, and the second stage of coprecipitation reaction is carried out until the particle size of the material is D 50The reaction is stopped after the particle size reaches 10-14 μm, and a precursor of a positive electrode material for a sodium ion battery is obtained through aging, washing, filtering and drying.
[0011] According to some preferred aspects of the present invention, the coprecipitation reaction is controlled to be carried out in a protective atmosphere or in the presence of an antioxidant, so as to prevent oxidation of the materials during the coprecipitation process.
[0012] In some embodiments of the present invention, the protective atmosphere is nitrogen, helium, argon or a combination thereof.
[0013] Preferably, the antioxidant is selected from a combination of one or more of vitamin B, hydrazine, carbohydrazide and isoascorbic acid.
[0014] Preferably, the nickel salt comprises one or a combination of at least two of nickel sulfate, nickel chloride or nickel nitrate;
[0015] Preferably, the ferrous salt comprises one or a combination of at least two of ferrous sulfate, ferrous chloride or ferrous nitrate;
[0016] Preferably, the manganese salt comprises one or a combination of at least two of manganese sulfate, manganese chloride or manganese nitrate;
[0017] Preferably, the copper salt comprises one or a combination of at least two of copper sulfate, copper chloride or copper nitrate;
[0018] Preferably, the absolute value of the pH difference is controlled to be 0.1-0.2.
[0019] Preferably, the first coprecipitation reaction and the second coprecipitation reaction adopt the same reaction temperature and stirring speed, the temperature of the reaction system is 40-55 ° C, and the stirring speed is 700-950 rpm.
[0020] Preferably, the alkaline solution is a NaOH solution.
[0021] A sodium ion battery positive electrode material precursor prepared by the above preparation method, the precursor is a core-shell structure, the core is nickel iron manganese hydroxide, the shell is copper iron manganese hydroxide, the precursor is a secondary particle formed by the agglomeration of primary particles, the morphology of the primary particles is flaky, the secondary particles are spherical or quasi-spherical, and the particle size D of the secondary particles is 50 10 - 14 μm, where the particle size D 50 The thickness of the shell is 8 - 10 μm and the thickness of the shell is 1 - 2 μm.
[0022] The core chemical formula is Ni x Fe y Mn 1-x-y (OH) 2, 0.2≤x≤0.6, 0.1≤y≤0.4, 1-xy≥0.2; the shell chemical formula is Cu a Fe b Mn 1-a-b (OH) 2 , 0<a≤0.3, 0.1≤b≤0.4, 1 - a - b ≥ 0.3.
[0023] A method for sintering a positive electrode material for a sodium ion battery comprises the following steps:
[0024] The sodium ion positive electrode material precursor of the present invention is sintered in two stages according to the system of the inner core and the outer shell. In the first stage, sodium salt is configured according to the sodium content required for the inner core. The sodium salt and the precursor are evenly mixed and ground, and then the inner core is sintered in an air or oxygen atmosphere. After the sintering is completed, the atmosphere is changed to nitrogen or argon and quenched. After that, the residual alkali on the surface is washed with water, and the sodium salt required for the outer shell is reconfigured to carry out the second stage of outer shell sintering.
[0025] Due to the differences between the core and shell systems, the required sintering temperatures are also different. Therefore, the core-shell structure positive electrode material is sintered in two stages. In the first stage, sodium salt is configured according to the sodium content required by the core. After the core is fired, the atmosphere is changed to nitrogen and quenched to ensure the stability of the core structure.
[0026] Preferably, sodium carbonate or sodium hydroxide is used as the sodium source, and the molar amount of sodium added is 0.95-1.1 times the total molar amount of the metal elements in the precursor.
[0027] Preferably, the sintering temperature of the inner core is lower than the sintering temperature of the outer shell.
[0028] Preferably, the inner core is sintered at a temperature of 700-900°C for a time of 10-16 h.
[0029] Preferably, the shell sintering temperature is 1000-1200°C and the time is 4-8 h.
[0030] An application of the above sodium ion positive electrode material precursor in sodium ion battery positive electrode material.
[0031] An application of the above-mentioned sodium ion battery positive electrode material in a sodium ion battery.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] (1) The use of a mixed complexing agent of ammonia water and oxalic acid in the co-precipitation process solves the problem of irregular precipitation of copper elements caused by the use of ammonia water alone. At the same time, the chelating reaction between oxalic acid and metal salt ions has a stronger complexing ability, which increases the reaction rate of metal elements in the solution and further improves the precursor yield.
[0034] (2) In the co-precipitation process, by using a mixed complexing agent of ammonia water and oxalic acid, the metal ions are more fully complexed, the primary particles are more densely packed, and the tap density is significantly improved.
[0035] (3) Two-stage co-precipitation reaction, the optimal growth environment makes the interface contact between the core and the shell closer, and the sphericity of the finished product is better (see Figure 1 , 2 ), the morphology is controllable and the precursor yield is good.
[0036] (4) The core-shell structured sodium ion battery cathode material synthesized by two-stage calcination has a discharge capacity of up to 160.1 mAh·g at 1 C -1 , only 147.06 mAh·g -1 The cycle capacity retention rate of the sample sintered twice after 300 cycles is as high as 61.34%, while that of the sample sintered once is only 42.85%, with good air stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a low-magnification scan of the sample in Example 1.
[0038] Figure 2 This is a low-magnification scan of the sample using only ammonia water as the complexing agent.
[0039] Figure 3 This is a high-magnification line scan image of the cross section of the sample in Example 1.
[0040] Figure 4 This is a high-magnification scan of Example 1.
[0041] Figure 5 This is a low-magnification scan of the sample in Example 4.
[0042] Figure 6 This is the XRD pattern of the sample in Example 1.
[0043] Figure 7 This is the XRD diagram of the sample in Example 4.
[0044] Figure 8 This is a comparison chart of the rate performance between mixed complexing agent and ammonia water only.
[0045] Fig. 9 This is a comparison chart of the rate performance between the first co-precipitation and the second co-precipitation.
[0046] Fig.10 This is a comparison chart of the rate performance of primary sintering and secondary sintering.
[0047] Fig.11 This is a comparison chart of the circulation performance of mixed complexing agent and ammonia water only.
[0048] Fig.12 This is a comparison chart of the cycle performance of primary co-precipitation and secondary co-precipitation.
[0049] Fig.13 This is a performance comparison chart of the primary sintering and secondary sintering cycles. DETAILED DESCRIPTION
[0050] The present invention will be further described below in conjunction with specific embodiments and accompanying drawings, but the present invention is not limited to the following embodiments. Unless otherwise defined, all professional terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0051] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0052] During the coprecipitation reaction: the concentration of the ammonia solution is 13 g / L, the concentration of oxalic acid is 9 g / L; the liquid alkali solution is a 2 mol / L sodium hydroxide aqueous solution; the nickel salt is nickel sulfate, the manganese salt is manganese sulfate, the ferrous salt is ferrous sulfate, and the copper salt is copper sulfate.
[0053] Example 1
[0054] This example provides a method for preparing a core-shell structure precursor with a core of nickel-iron-manganese hydroxide and a shell of copper-iron-manganese hydroxide, which specifically includes the following steps:
[0055] Add pure water to the reactor and heat to 50°C, add the prepared alkaline solution to adjust the pH value of the bottom solution to 11, stir the solution evenly at a speed of 750r / min inside the reactor with the stirring blade, and prepare the bottom solution for the coprecipitation reaction. Pump 2mol / L nickel-iron-manganese mixed salt solution (configured according to [Ni:Fe:Mn] = 4:2:4) at a flow rate of 5.0mL / min, 2mol / L sodium hydroxide solution at a flow rate of 5.0mL / min, and 5% oxalic acid and 95% ammonia complexing agent solution at a flow rate of 5.0mL / min into the reactor at the same time. Keep the pH value of the reactor at 11 and react for 6 hours (at this time, the core D 50The particle size is 8 μm). After the core is formed, the ratio of the complexing agent is changed to 10% oxalic acid and 90% ammonia. The pH setting is changed to 9.5. After the pH is stable, 2 mol / L copper-iron-manganese mixed solution (configured according to [Cu:Fe:Mn] = 2.2:3:4.8) is added, and the reaction is continued until the median particle size of the product reaches 12 μm. The slurry is pumped to the aging tank through the discharge port. After aging, centrifugation, drying, screening, and packaging, the product is completed. The core is nickel-iron-manganese-based and the shell is copper-iron-manganese-based. The core molecular formula of the precursor is Ni 0.4 Fe 0.2 Mn 0.4 (OH) 2 , the molecular formula of the outer shell is Cu 0.22 Fe 0.3 Mn 0.48 (OH) 2 , D 50 The particle size is about 12 μm and the tap density is 2.22 g / cm 3 The IPC results of the samples obtained in Example 1 are shown in Table 1.
[0056] Figure 1 This is a low-magnification scan of the sample in Example 1. Figure 1 It can be seen that the overall shape is spherical, D 50 The particle size is about 12 μm, and the secondary particles have a full morphology. Figure 3 This is a high-magnification line scan of the cross section of the sample in Example 1. Figure 3 It can be seen that the overall shape is spherical, with the outer shell containing three elements: copper, iron and manganese, and the inner core containing three elements: nickel, iron and manganese. Figure 4 This is a high-magnification scan of Example 1. Figure 4 It can be seen that the primary particles are composed of flakes and are tightly connected. Figure 5 This is a low-magnification scan of the sample in Example 4. The primary particles are block-shaped, and the secondary particles are uniform and dense. Figure 6 The XRD pattern of the sample in Example 1 is shown in Figure 1. The sample can well match the standard PDF card of nickel hydroxide phase (#14-0117). 2+ Fe with a smaller radius 2+ With Mn 2+ According to the Bragg equation (2dsinθ = nλ), the XRD peak will shift to a higher angle.
[0057] Table 1 ICP results of mixed complexing agent samples (Example 1)
[0058]
[0059] Comparative Example 1
[0060] In this comparative example, the complexing agent for the first and second precipitations is different from that in Example 1. The complexing agent is 100% ammonia water. Other implementation conditions are the same as those in Example 1. The tap density of the obtained sample is 0.81 g / cm 3 , the IPC results are shown in Table 2:
[0061] Table 2 ICP results of samples using only ammonia (comparative sample)
[0062]
[0063] The use of a mixed complexing agent of ammonia water and oxalic acid increases the reaction rate of metal elements in the solution, further improves the precursor yield, makes the metal ions more fully complexed, and makes the primary particles more densely stacked, thereby significantly improving the tap density.
[0064] Comparative Example 2
[0065] The precipitation operation of this comparative example is different from that of Example 1, specifically, pure water is added to the reactor and heated to 50°C, the configured alkaline solution is added to adjust the pH value of the bottom liquid to 11, and the stirring blade inside the reactor mixes the solution evenly at a speed of 750r / min to prepare the bottom liquid of the coprecipitation reaction. 2mol / L nickel-iron-manganese-copper mixed salt solution (configured according to [Ni:Fe:Mn:Cu] = 2.8:2.3:4.24:0.66) is pumped into the reactor at a flow rate of 5.0mL / min, 2mol / L sodium hydroxide solution is pumped at a flow rate of 5.0mL / min, oxalic acid accounts for 5%, and ammonia water accounts for 95% of the complexing agent solution is pumped into the reactor at a flow rate of 5.0mL / min, and the reactor is kept at a pH value of 11 for 12 hours. The other implementation conditions are the same as those of Example 1. The IPC results of the samples obtained in Comparative Example 2 are shown in Table 3:
[0066] Table 3 ICP results of single coprecipitation sample (comparative sample)
[0067]
[0068] Example 2
[0069] Add pure water to the reactor and heat it to 50°C, add the prepared alkaline solution to adjust the pH value of the bottom solution to 11, stir the solution evenly at a speed of 750r / min inside the reactor with the stirring blade, and prepare the bottom solution for the coprecipitation reaction. Pump 2mol / L nickel-iron-manganese mixed salt solution (configured according to [Ni:Fe:Mn] = 6:2:2) at a flow rate of 5.0mL / min, 2mol / L sodium hydroxide solution at a flow rate of 5.0mL / min, and a complexing agent solution with 10% oxalic acid and 90% ammonia at a flow rate of 5.0mL / min into the reactor at the same time. Keep the pH value of the reactor at 11 and react for 6 hours (at this time, the core D50 The particle size is 8 μm). After the core is formed, the ratio of the complexing agent is changed to 20% oxalic acid and 80% ammonia. The pH setting is changed to 9.5. After the pH is stable, 2 mol / L copper-iron-manganese mixed solution (configured according to [Cu:Fe:Mn] = 1:3:6) is added, and the reaction is continued until the median particle size of the product reaches 12 μm. The slurry is pumped to the aging tank through the discharge port. After aging, centrifugation, drying, screening, and packaging, the product is completed. The core is nickel-iron-manganese-based and the shell is copper-iron-manganese-based. The core molecular formula of the precursor is Ni 0.6 Fe 0.2 Mn 0.2 (OH) 2 , the molecular formula of the outer shell is Cu 0.1 Fe 0.3 Mn 0.6 (OH) 2 , D 50 The particle size is about 12 μm and the tap density is 2.42 g / cm 3 The IPC results of the samples obtained in Example 2 are shown in Table 4:
[0070] Table 4 ICP results of mixed complexing agent samples (Example 2)
[0071]
[0072] Example 3
[0073] Add pure water to the reactor and heat to 50°C, add the prepared alkaline solution to adjust the pH value of the bottom solution to 9, stir the solution evenly at a speed of 750r / min inside the reactor with the stirring blade, and prepare the bottom solution for the coprecipitation reaction. Pump 2mol / L nickel-iron-manganese mixed salt solution (configured according to [Ni:Fe:Mn] = 2:4:4) at a flow rate of 5.0mL / min, 2mol / L sodium hydroxide solution at a flow rate of 5.0mL / min, and oxalic acid accounting for 5% and ammonia accounting for 95% of the complexing agent solution at a flow rate of 5.0mL / min into the reactor at the same time. Keep the pH value of the reactor at 9 and react for 6 hours (at this time, the core D 50 The particle size is 10 μm). After the core is formed, the ratio of the complexing agent is changed to 10% oxalic acid and 90% ammonia. The pH setting is changed to 8.5. After the pH is stable, 2 mol / L copper-iron-manganese mixed solution (configured according to [Cu:Fe:Mn] = 3:2:5) is added, and the reaction is continued until the median particle size of the product reaches 14 μm. The slurry is pumped to the aging tank through the discharge port. After aging, centrifugation, drying, screening, and packaging, the product is completed. The core is nickel-iron-manganese-based and the shell is copper-iron-manganese-based. The core molecular formula of the precursor is Ni 0.2 Fe 0.4 Mn0.4 (OH) 2 , the molecular formula of the outer shell is Cu 0.3 Fe 0.2 Mn 0.5 (OH) 2 , D 50 The particle size is about 14μm and the tap density is 2.12g / cm 3 The IPC results of the samples obtained in Example 3 are shown in Table 5:
[0074] Table 5 ICP results of mixed complexing agent samples
[0075]
[0076] Example 4
[0077] This example provides a method for preparing a core-shell structure sodium ion positive electrode material with a core of sodium nickel iron manganese oxide and a shell of sodium copper iron manganese oxide, which specifically comprises the following steps:
[0078] The precursor obtained in Example 1 was mixed with the sodium carbonate required for the core. After being fully mixed and ground, the mixture was placed in a muffle furnace and heated to 500°C for pre-sintering for 3 hours to melt the sodium source. The mixture was then heated to 700°C and kept warm for 16 hours. The oxygen flow rate during the inner core firing was 2.0 mL / min. After the inner core was fired, the atmosphere was switched to nitrogen and quenched. After the residual alkali on the surface was washed with water, the sodium source required for the outer shell was replenished. After pre-sintering at 500°C for 3 hours to melt the sodium source, the mixture was heated to 1000°C at a heating rate of 5°C / min and sintered for 8 hours until the core-shell structure was fired. Thus, a core-shell structure sodium ion positive electrode material was obtained.
[0079] Figure 5 This is a low-magnification scan of the sample of this embodiment. It can be seen from the figure that the primary particles are blocky and the secondary particles are uniform and dense. Figure 7 This is the XRD diagram of the sample in this embodiment. Since the core and the shell in this diagram are both O3-type positive electrode materials for sodium ion batteries, their XRD peaks can well match the standard PDF card (#54-0887) for the O3 phase of positive electrode materials for sodium ion batteries. Figure 8 This is the rate performance diagram of the sample in this example. It still has 60 mAh·g at 10 C. -1 Its capacity and rate performance are significantly better than those of conventional nickel-cobalt-manganese materials, which shows its excellent electrochemical properties.
[0080] Comparative Example 3
[0081] The precursor in Example 4 was replaced by the sample obtained in Comparative Example 1, and the other conditions were the same as those in Example 4. The electrochemical properties of the samples obtained in Example 4 and Comparative Example 3 are shown in FIG. Figure 8 and Fig.11 Show, Figure 8 It shows that at each rate, the performance of the samples prepared by mixed complexing agents is better. Fig.11 It can be seen that the cycle capacity retention rate of the sample using a mixed complexing agent after 300 cycles is as high as 61.36%, while that of the sample using only ammonia water as the complexing agent is only 16.27%.
[0082] Comparative Example 4
[0083] The precursor in Example 4 was replaced by the sample obtained in Comparative Example 2, and the other conditions were the same as those in Example 4. The electrochemical properties of the samples obtained in Example 4 and Comparative Example 4 are shown in FIG. Fig. 9 and Fig.12 Show: by Fig. 9 It can be seen that compared with the mixed complexing agent co-precipitation once, the rate performance of the sample prepared by the mixed complexing agent secondary co-precipitation is significantly improved; Fig.12 It can be seen that the cycle capacity retention rate of the sample prepared by secondary co-precipitation after 300 cycles is as high as 61.36%, while that of the sample prepared by single co-precipitation is only 26.72%.
[0084] Comparative Example 5
[0085] The sintering steps of this comparative example are different from those of Example 4. Specifically, the precursor obtained in Example 1 is mixed with the sodium carbonate required for the core. After being fully mixed and ground, the mixture is placed in a muffle furnace and heated to 500°C for pre-sintering for 3 hours to melt the sodium source. The mixture is then heated to 1000°C and kept warm for 24 hours. The oxygen flow rate during the inner core firing is 2.0 mL / min until the core-shell structure is fired to obtain a core-shell structure sodium ion positive electrode material. Other implementation conditions are the same as those of Example 4.
[0086] The electrochemical properties of the samples obtained in Example 4 and Comparative Example 5 are as follows: Fig.10 and Fig.13 Show, Fig.10 It can be seen from the rate performance that the performance of the samples sintered twice is better than that of the samples sintered once at all rates. Fig.13 It can be seen that the cycle capacity retention rate of the second-sintered sample after 300 cycles is as high as 61.36%, while that of the sample sintered once is only 42.85%.
[0087] Example 5
[0088] The precursor obtained in Example 1 was mixed with sodium carbonate. After being fully mixed and ground, the mixture was placed in a muffle furnace and heated to 500°C for pre-sintering for 3 hours to melt the sodium source. The mixture was then heated to 800°C and kept warm for 16 hours. The oxygen flow rate during the inner core firing was 2.0 mL / min. After the inner core was fired, the atmosphere was switched to nitrogen and quenched. After the residual alkali on the surface was washed with water, the sodium source required for the outer shell was replenished. After pre-sintering at 500°C for 3 hours to melt the sodium source, the mixture was heated to 1100°C at a heating rate of 5°C / min and sintered for 8 hours until the core-shell structure was fired, thereby obtaining a core-shell structure sodium ion positive electrode material.
[0089] Example 6
[0090] The precursor obtained in Example 1 was mixed with the sodium hydroxide required for the core. After being fully mixed and ground, the mixture was placed in a muffle furnace and heated to 500°C for pre-sintering for 3 hours to melt the sodium source. The mixture was then heated to 700°C and kept warm for 16 hours. The oxygen flow rate during the inner core firing was 2.0 mL / min. After the inner core was fired, the atmosphere was switched to nitrogen and quenched. After the residual alkali on the surface was washed with water, the sodium source required for the outer shell was replenished. After pre-sintering at 500°C for 8 hours to melt the sodium source, the mixture was heated to 1000°C at a heating rate of 5°C / min and sintered for 8 hours until the core-shell structure was fired. Thus, a core-shell structure sodium ion positive electrode material was obtained.
[0091] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a precursor of a positive electrode material for a sodium ion battery, characterized in that: The steps include: (1) preparing a mixed salt solution A of nickel, ferrous iron and manganese, a mixed salt solution B of copper, ferrous iron and manganese, mixed complexing agent solutions C and D of ammonia water and oxalic acid, an alkali solution and a reaction kettle bottom liquid, wherein the molar mass of oxalic acid in the complexing agent solution C accounts for 5-10% and the molar mass of ammonia water accounts for 90-95%; and the molar mass of oxalic acid in the complexing agent solution D accounts for 10-30% and the molar mass of ammonia water accounts for 70-90%; (2) A mixed salt solution A, an alkaline solution and a complexing agent solution C are introduced into a reactor containing a reactor bottom liquid in parallel, and the pH value is controlled to be 9-11 to carry out a first stage of coprecipitation reaction; after the particle size D50 of the prepared material reaches 8-10 μm, a mixed salt solution B, an alkaline solution and a complexing agent solution D are introduced into the reactor in parallel, and the pH value is controlled to be 8.5-10.5 to carry out a second stage of coprecipitation reaction, and the reaction is stopped after the particle size D50 of the material reaches 10-14 μm. After aging, washing, filtering and drying, a precursor of a positive electrode material for a sodium ion battery is obtained.
2. The method for preparing a precursor of a positive electrode material for a sodium ion battery according to claim 1, characterized in that: The first stage coprecipitation reaction and the second stage coprecipitation reaction are carried out in a protective atmosphere or in the presence of an antioxidant.
3. The method for preparing a precursor of a positive electrode material for a sodium ion battery according to claim 2, characterized in that: The protective atmosphere is one or more of nitrogen, helium or argon.
4. The method for preparing a precursor of a positive electrode material for a sodium ion battery according to claim 2, characterized in that: The antioxidant is one or more selected from vitamin B, hydrazine, carbohydrazide and isoascorbic acid.
5. The method for preparing a precursor of a positive electrode material for a sodium ion battery according to claim 1, characterized in that: The nickel salt includes one or a combination of at least two of nickel sulfate, nickel chloride or nickel nitrate; and / or, the ferrous salt includes one or a combination of at least two of ferrous sulfate, ferrous chloride or ferrous nitrate; and / or, the manganese salt includes one or a combination of at least two of manganese sulfate, manganese chloride or manganese nitrate; and / or, the copper salt includes one or a combination of at least two of copper sulfate, copper chloride or copper nitrate.
6. The method for preparing a precursor of a positive electrode material for a sodium ion battery according to claim 1, characterized in that: The absolute value of the solution pH deviation during the reaction was 0.1-0.
2.
7. The method for preparing a precursor of a positive electrode material for a sodium ion battery according to claim 6, characterized in that: The first coprecipitation reaction and the second coprecipitation reaction adopt the same reaction temperature and stirring speed, the temperature of the reaction system is 40-55 ° C, and the stirring speed is 700-950rpm.
8. The method for preparing a precursor of a positive electrode material for a sodium ion battery according to claim 7, characterized in that: The alkaline solution is a NaOH solution.
9. A sodium ion battery cathode material precursor, characterized in that: The precursor is a core-shell structure, the core is nickel-iron-manganese hydroxide, the shell is copper-iron-manganese hydroxide, the precursor is a secondary particle formed by the agglomeration of primary particles, the primary particles are flaky in shape, the secondary particles are spherical or quasi-spherical, the particle size D50 of the secondary particles is 10-14 μm, wherein the particle size D50 of the core is 8-10 μm, and the shell thickness is 1-2 μm; The core chemical formula is Ni x Fe y Mn 1-x-y (OH)2, 0.2≤x≤0.6, 0.1≤y≤0.4, 1-xy≥0.2; the shell chemical formula is Cu a Fe b Mn 1-a-b (OH)2, 0 < a≤0.3, 0.1≤b≤0.4, 1-ab≥0.
3.
10. The sodium ion battery positive electrode material precursor according to claim 9, characterized in that: The sodium ion battery positive electrode material precursor is prepared by the method for preparing a sodium ion battery positive electrode material precursor according to any one of claims 1 to 8.
11. A method for sintering a positive electrode material for a sodium ion battery, characterized in that: It is prepared from the precursor described in any one of claims 9-10, and is sintered in two stages according to the system of the inner core and the outer shell. In the first stage, sodium salt is configured according to the sodium content required for the inner core. The sodium salt and the precursor are evenly mixed and ground, and then the inner core is sintered in an air or oxygen atmosphere. After the sintering is completed, the atmosphere is changed to nitrogen or argon and quenched. After that, the residual alkali on the surface is washed with water, and the sodium salt required for the outer shell is reconfigured to carry out the second stage of outer shell sintering.
12. The sintering method of the sodium ion battery positive electrode material according to claim 11, characterized in that: Sodium carbonate or sodium hydroxide is used as the sodium source, and the molar amount of sodium added is 0.95-1.1 times the total molar amount of the metal elements in the precursor.
13. The sintering method of the sodium ion battery positive electrode material according to claim 12, characterized in that: The sintering temperature of the inner core is lower than that of the outer shell.
14. The sintering method of the sodium ion battery positive electrode material according to claim 13, characterized in that: The core sintering temperature is 700-900°C and the time is 10-16 h; The shell sintering temperature is 1000-1200°C and the time is 4-8 h.
15. A sodium ion battery positive electrode material, characterized in that: The sintering method is prepared by any one of claims 11 to 14.
16. Use of the sodium ion battery positive electrode material precursor according to any one of claims 9 to 10 in sodium ion battery positive electrode materials.
17. Use of the sodium ion battery positive electrode material prepared by the sintering method according to any one of claims 11 to 14 in sodium ion batteries.
Citation Information
Patent Citations
Layered oxide positive electrode material, preparation method thereof and sodium ion battery
CN115148978A
O3-P2 composite phase sodium ion positive electrode material as well as preparation method and application thereof
CN115148984A
Sodium ion positive electrode material and preparation method and application thereof
CN115557546A
Sodium ion positive electrode material precursor, and preparation method and application thereof
CN117088425A
Sodium ion positive electrode material and preparation method and application thereof
CN117597798A